1987
DOI: 10.1099/0022-1317-68-5-1317
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Protease Cleavage Sites Involved in the Formation of the Envelope Glycoprotein and Three Non-structural Proteins of Dengue Virus Type 2, New Guinea C Strain

Abstract: SUMMARYAmino terminal sequences of the envelope protein E and the three largest nonstructural proteins NS1, NS3, and NS5 of the New Guinea C strain of dengue virus type 2 (DEN-2) were obtained by nucleotide and protein sequencing. Clones were prepared containing cDNA of DEN-2 virus in the plasmid pUC8. The nucleotide sequences of viral cDNA inserts were determined and the cDNA of each clone positioned on the flavivirus genomic map by comparison of the deduced amino acid sequence with that of yellow fever virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 42 publications
1
25
1
Order By: Relevance
“…We observed that the protein molecular mass is not exactly the same as described by other authors (Se- Thoe et al 1999). In this context, it is important to have in mind that the heterogeneity in the molecular mass of those proteins could be explained by both viral and host proteases that may be involved in processing the flavivirus proteins (Biedryzcka et al 1987). Moreover, it is known that some flavivirus proteins reach different migration levels in SDS gels considering the intracellular and virion-associated forms (Wright & Westaway 1977, Svitkin et al 1984.…”
contrasting
confidence: 45%
“…We observed that the protein molecular mass is not exactly the same as described by other authors (Se- Thoe et al 1999). In this context, it is important to have in mind that the heterogeneity in the molecular mass of those proteins could be explained by both viral and host proteases that may be involved in processing the flavivirus proteins (Biedryzcka et al 1987). Moreover, it is known that some flavivirus proteins reach different migration levels in SDS gels considering the intracellular and virion-associated forms (Wright & Westaway 1977, Svitkin et al 1984.…”
contrasting
confidence: 45%
“…viruses (Rice et al, 1985(Rice et al, , 1986aBiedrzycka et al, 1987). The matched nucleotide and amino acid sequences for KUN virus at the cleavage sites are shown in Fig.…”
Section: Location Of Each Of the Ns Proteins In The Polyprotein Sequencementioning
confidence: 99%
“…Where the amino acid residue in position -3 is not a short side chain amino acid, a cluster of three basic amino acids occurs. Sources of sequence data are as follows: WN virus (Castle et al, 1986), MVE virus (Dalgarno et aL, 1986), JE virus (Sumiyoshi et aL, 1986), SLE virus (Trent et al, 1987), YF virus (Rice et al, 1985) and DEN-2 virus (Biedrzycka et aL, 1987;P J. Wright, personal communication) endoplasmic reticulum (ER). Hence KUN NS 1 appears likely to be cleaved by signal peptidase.…”
Section: Characterization Of Cleavage Sitesmentioning
confidence: 99%
“…In contrast, the amino termini of proteins NS2B, NS3, NS4A and NS5 are preceded by a protease consensus sequence which contains multiple basic amino acid residues (Rice et al, 1985(Rice et al, , 1986Biedrzycka et al, 1987;Speight et al, 1988;Chambers et al, 1989;Wright et al, 1989;Wengler et al, 1990) and it has been proposed that a cytosolic virus-encoded protease which cleaves after double basic residues is responsible for the corresponding proteolytic cleavages (Rice et al, 1985;Speight et al, 1988). Recently, a computer search of conserved amino acid residues has led to the suggestion that the amino-terminal segment of the NS3 protein represents a serine protease (Bazan & Fletterick, 1989;Gorbalenya et al, 1989).…”
Section: Introductionmentioning
confidence: 99%